Frailty Is Associated With Worse Outcomes In Geriatric Pelvic Fractures. Issue 7 (July 2022) - Perea, Lindsey L.; Fort, Launick Saint; Morgan, Madison E.; Brown, Catherine Ting; Wang, Steadman; Bradburn, Eric
Frail, geriatric patients with pelvic fractures can present differently than non-frail patients. Using the Clinical Frailty Scale(CFS), a retrospective analysis was conducted to determine the relationship between patients' CFS and outcomes after pelvic fractures. We hypothesized that frail, geriatric trauma patients defined as a CFS>4 with pelvic fractures have worse outcomes than non-frail patients with a CFS≤4 despite similar injuries. All geriatric patients with pelvic fractures and documented CFS were included. Seventy patients were included, with 59% (n = 41) frail. The groups were compared with no difference in mortality. The frail group was older and were most likely discharged to a skilled nursing facility (65.8%). Non-frail were most likely discharged to acute rehab (52%). Frail had lower functional status at discharge (median: 14.5v.16, P = .015). Frail patients had worse overall outcomes in this analysis of geriatric pelvic fracture patients. Special attention should focus on this vulnerable population to ensure optimal treatment and outcomes.